A Na+/K+ ATPase Pump Regulates Chondrocyte Differentiation and Bone Length Variation in Mice - Marchini, Marta; Ashkin, Mitchell R.; Bellini, Melina; Sun, Margaret Man-Ger; Workentine, Matthew Lloyd; Okuyan, Hamza Malik; Krawetz, Roman; Beier, Frank; Rolian, Campbell (Frontiers in Cell and Developmental Biology, 2021)
The genetic and developmental mechanisms involved in limb formation are relatively well documented, but how these mechanisms are modulated by changes in chondrocyte physiology to produce differences in limb bone length remains unclear. Here, using tibia and cell cultures we show a dynamic role for the cell membrane-bound Na/K ATPase pump (NKA) in chondrocyte differentiation and in bone length regulation. NKA inhibition disrupts chondrocyte differentiation by upregulating expression of mesenchymal stem cell markers (Prrx1, Serpina3n), downregulation of chondrogenesis marker Sox9, and altered expression of extracellular matrix genes (e.g., collagens) associated with proliferative and hypertrophic chondrocytes. We also show that Fxyd2, a facultative NKA subunit which modulates pump efficiency, may be involved in proliferative and hypertrophic chondrocyte maturation. Using RNAseq, we find that altered expression of Fxyd2, along with key endochondral ossification genes such as with Npr3, Dlk1, Sox9, and Sfrp1, is associated with variation in limb length in Longshanks, a mouse model of experimental evolution, suggesting a broader evolutionary role of NKA modulation in limb length diversity.